Comprehensive Profile of Acute Mitochondrial Dysfunction in a Preclinical Model of Severe Penetrating TBI - Pandya, Jignesh D.; Leung, Lai Yee; Yang, Xiaofang; Flerlage, William J.; Gilsdorf, Janice S.; Deng-Bryant, Ying; Shear, Deborah A. (Frontiers in Neurology, 2019)
Mitochondria constitute a central role in brain energy metabolism, and play a pivotal role in the development of secondary pathophysiology and subsequent neuronal cell death following traumatic brain injury (TBI). Under normal circumstances, the brain consumes glucose as the preferred energy source for adenosine triphosphate (ATP) production over ketones. To understand the comprehensive picture of substrate-specific mitochondrial bioenergetics responses following TBI, adult male rats were subjected to either 10% unilateral penetrating ballistic-like brain injury (PBBI) or sham craniectomy (n=5 animals per group). At 24 hours post-injury, mitochondria were isolated from pooled brain regions (frontal cortex and striatum) of the ipsilateral hemisphere. Mitochondrial bioenergetics parameters were measured ex vivo in the presence of four sets of metabolic substrates: pyruvate+malate (PM), glutamate+malate (GM), succinate (Succ), and β-hydroxybutyrate+malate (BHBM). Additionally, mitochondrial matrix dehydrogenase activities (i.e. pyruvate dehydrogenase complex (PDHC), alpha-ketoglutarate dehydrogenase complex (α-KGDHC) and glutamate dehydrogenase (GDH)) and mitochondrial membrane-bound dehydrogenase activities (i.e. electron transport chain (ETC) Complex I, II, and IV) were compared between PBBI and sham groups. Furthermore, mitochondrial coenzyme contents, including NAD(t) and FAD(t), were quantitatively measured in both groups. Collectively, PBBI led to an overall significant decline in the ATP synthesis rates (43-50%; *p<0.05 vs. sham) when measured using each of the four sets of substrates. The PDHC and GDH activities were significantly reduced in the PBBI group (42-53%; *p<0.05 vs. sham), whereas no significant differences were noted in α-KGDHC activity between groups. Both Complex I and Complex IV activities were significantly reduced following PBBI (47-81%; *p<0.05 vs. sham), whereas, Complex II activity was comparable between groups. The NAD(t) and FAD(t) contents were significantly decreased in the PBBI group (27-35%; *p<0.05 vs. sham). The decreased ATP synthesis rates may be due to the significant reductions in brain mitochondrial dehydrogenase activities and coenzyme contents observed acutely following PBBI. These results provide a basis for the use of “alternative biofuels” for achieving higher ATP production following severe penetrating brain trauma.